Association Between Germline Mutation in VSIG10L and Familial Barrett Neoplasia - Fecteau, Ryan E. (JAMA Oncol, 2016)
IMPORTANCE: Esophageal adenocarcinoma and its precursor lesion Barrett esophagus have seen a dramatic increase in incidence over the past 4 decades yet marked genetic heterogeneity of this disease has precluded advances in understanding its pathogenesis and improving treatment. OBJECTIVE: To identify novel disease susceptibility variants in a familial syndrome of esophageal adenocarcinoma and Barrett esophagus, termed familial Barrett esophagus, by using high-throughput sequencing in affected individuals from a large, multigenerational family. DESIGN, SETTING, AND PARTICIPANTS: We performed whole exome sequencing (WES) from peripheral lymphocyte DNA on 4 distant relatives from our multiplex, multigenerational familial Barrett esophagus family to identify candidate disease susceptibility variants. Gene variants were filtered, verified, and segregation analysis performed to identify a single candidate variant. Gene expression analysis was done with both quantitative real-time polymerase chain reaction and in situ RNA hybridization. A 3-dimensional organotypic cell culture model of esophageal maturation was utilized to determine the phenotypic effects of our gene variant. We used electron microscopy on esophageal mucosa from an affected family member carrying the gene variant to assess ultrastructural changes. MAIN OUTCOMES AND MEASURES: Identification of a novel, germline disease susceptibility variant in a previously uncharacterized gene. RESULTS: A multiplex, multigenerational family with 14 members affected (3 members with esophageal adenocarcinoma and 11 with Barrett esophagus) was identified, and whole-exome sequencing identified a germline mutation (S631G) at a highly conserved serine residue in the uncharacterized gene VSIG10L that segregated in affected members. Transfection of S631G variant into a 3-dimensional organotypic culture model of normal esophageal squamous cells dramatically inhibited epithelial maturation compared with the wild-type. VSIG10L exhibited high expression in normal squamous esophagus with marked loss of expression in Barrett-associated lesions. Electron microscopy of squamous esophageal mucosa harboring the S631G variant revealed dilated intercellular spaces and reduced desmosomes. CONCLUSIONS AND RELEVANCE: This study presents VSIG10L as a candidate familial Barrett esophagus susceptibility gene, with a putative role in maintaining normal esophageal homeostasis. Further research assessing VSIG10L function may reveal pathways important for esophageal maturation and the pathogenesis of Barrett esophagus and esophageal adenocarcinoma.